The challenges in the adoption of fertigation system in Johor - Johan, Siti Fatimah (2018)
Population of Malaysia is increasing drastically over the years. This cause the demand on food also increases. However, the self-sufficient level still does not achieve to 100%. Therefore, the agriculture sector had changed its trend because of the development of agriculture sector and because of the consumption patterns. It resulted to majority of the farmers seek to maximum yield and produce high quality food-based products. Therefore, the adoption of fertigation system had become main choice for agriculture producers especially vegetables producers. The purpose of this study is to determine challenges in the adoption of fertigation system in Johor. This include to find out the association between socio-demographic and the rate of adoption and also to find out the challenges that influence the rate of adoption. A sample of 60 respondents was selected from 10 districts in Johor. 6 respondents were chosen to represents each districts. The data collected were analyzed by using descriptive analysis, chi-square analysis and factor analysis. The findings is majority of the farmers still adopted this system in small scale farming and only chili crops had become a main crops among the farmers. From chi-square analysis, only gender and education level had an association with the rate of adoption. The factor analysis had concluded that there are three main challenges factor that could affect the rate of adoption. A first challenge is innovation where it could become a barrier depending on the attributes of the technology. Second, communication challenges had become problems when the spreading of the information is not widely. Lastly, the social system could become challenges when there is no motivation and influence from the society.